Albion's dream - Norman, Roger (London : Faber and Faber, 1990)
Edward's involvement with a mysterious adventure game leads to a confrontation with his boarding school's tyrannical headmaster and evil doctor.
5-8.
English.
Keywords: Adventure games -- Fiction; Fantasy games -- Fiction; Games -- Fiction; Schools -- Fiction; Supernatural -- Fiction; Adventure games -- Fiction; Fantasy games -- Fiction; Games -- Fiction; Supernatural -- Fiction